0709 Self-Reported and Actigraphic Short Sleep Duration in Older Persons. (12th April 2019) - Miner, Brienne; MHS, M D; Stone, Katie; Hajduk, Alexandra; Yaggi, Henry K; Redeker, Nancy; Fragoso, Carlos Vaz
Abstract: Introduction: Short sleep duration (SSD), i.e., lasting ≤6 hours, is associated with adverse health outcomes. The epidemiology of SSD has not yet been established in older persons, including the distinction between self-reported vs. actigraphy measured sleep time and the presence or absence of coexisting poor sleep quality. Methods: Using data on 5, 717 older persons from the Study of Osteoporotic Fractures and the Osteoporotic Fractures in Men Sleep Study, we calculated the prevalence of self-reported and actigraphic SSD with and without poor sleep quality, respectively. The Pittsburgh Sleep Quality Index (PSQI) evaluated self-reported sleep duration and poor sleep quality (PSQI score >5), whereas results from wrist actigraphy were averaged over approximately 5 days. Next, we examined the agreement between self-reported and actigraphic SSD and the correlates associated with discordance, using multivariate logistic regression. Correlates included age, sex, race, poor sleep quality, and impairments in cognition (MMSE <24 in women; Teng 3MS <82 in men) and physical function (inability to do a chair stand). Results: Mean age was 80 years (SD 5.8); 50% were female and 90% were white. Self-reported and actigraphic SSD were established in 767 (13.4%) and 1, 617 (28.3%) participants, respectively. Among those with self-reported SSD, 728 (94.9%) reported poor sleep quality. Among those with actigraphic SSD, 812 (50%) reported poor sleep quality. The correlation between self-reported and actigraphic SSD was poor (κ= 0.11). In particular, a total of 1, 294 (22.6%) participants had actigraphic SSD but not self-reported SSD, whereas a total of 444 (7.8%) participants had self-reported SSD but not actigraphic SSD. The odds of discordance in self-reported vs. actigraphic SSD were significantly higher among males (1.19 [1.02, 1.39]), non-whites (1.67 [1.36, 2.06]), and participants with poor sleep quality (1.68 [1.48, 1.90]) or physical impairment (1.28 [1.06, 1.54]). Conclusion: In older persons, self-reported and actigraphic SSD were poorly correlated, most evident in participants who were male, non-white, or had poor sleep quality or impaired physical function. Hence, the epidemiologic evaluation of SSD in older persons, including associations with adverse health outcomes, should include actigraphy-measured sleep duration. Support (If Any): None